Kekuatan Genggaman Tangan pada Pasien Post Stroke - Rumentalia Sulistini; Musonathul Khasifah; Hanna DL Damanik (Jurnal Surya Medika (JSM), 2021)
Stroke is a loss of brain function caused by the cessation of blood supply in part of the brain. Death of brain tissue due to stroke can cause muscle weakness in the affected limb such as fingers. This condition affects the ability to move and the quality of life of patients. Patients not only experience paralysis but also experience cognitive impairment, communication disorders, and visual field disorders or deficits in perception. Aims this study was to describe handgrip strength The average age of respondents was 60.5 years with the youngest age 41 years and 80 years of age. The average strength of the handgrip is 7.4 kg with the lowest strength is 1.3 kg and the highest is 18.6 kg. Obtained a relationship between age and muscle strength after stroke (p 0.023). The relationship between age and post-stroke muscle strength shows that the relationship between medium strength and negative patterning means that as you age, muscle strength decreases. So it is necessary to develop the Pattern of Activities and exercises for Post Stroke in Hospitals and the Community.